PAI-1 Concentrations in First-degree Relatives of Patients with Non-insulin-dependent Diabetes: Metabolic and Genetic Associations - Mansfield, Michael W; Stickland, Max H; Grant, Peter J (Thrombosis and Haemostasis, 1997)
Aim: To identify whether levels of PAI-1 are elevated in relatives of NIDDM patients and the extent to which they relate to features of insulin resistance and to genotype at a common PAI-1 promoter polymorphism.Results: In 132 first-degree relatives of NIDDM patients and 151 controls PAI-1 activity was higher in relatives 14.4 U/ml than controls U/ml (p <0.0005) with higher body mass index 27.3 v. 24.7 kg/m2 p <0.0005, fasting insulin 9.3 v. 7.6 mU/l p <0.005 and triglyceride v. 1.2 mmol/1 p <0.05. PAI-1 activity levels were higher in men and in smokers and showed a trend to being higher with increasing number of 4G alleles at the PAI-1 promoter polymorphism. After adjustment for age, sex, smoking, BMI and triglyceride levels, PAI-1 levels remained 26% higher in the NIDDM relatives (p = 0.01).Conclusion: In relatives of NIDDM patients PAI-1 levels are elevated, presenting an additional mechanism for their increased cardiovascular risk.